The Role of The Gresik Regency Manpower Office in Vocational Training at the Gresik Regency Vocational House - Rania Riska Vindy Aprilia; Indira Arundinasari (Univiversitas Dr. Djar Wattiheluw, 2024)
The Gresik Regency Government aims to reduce its 2023 unemployment rate of 6.82% through the Vocational Home Education and Training program, the only one of its kind in Indonesia. The success of this program relies heavily on the active role of the Gresik Regency Manpower Office. This study aims to analyze the office’s role in vocational education and training at the Vocational House, using a qualitative descriptive approach based on Jones’ public sector role theory. The findings show that while the Gresik Manpower Office has been effective in implementing and supervising the program, its impact on reducing unemployment remains limited, requiring further efforts to make significant progress.